PEMODELAN KINETIKA DAN OPTIMASI PEMBERIAN CEKAMAN MANGAN PADA KULTUR SPIROGYRA SP. UNTUK MENINGKATKAN AKUMULASI LIPID SEBAGAI SUMBER OMEGA-3 DENGAN PENDEKATAN RESPONSE SURFACE METHODOLOGY - Desy Silalahi, Lusia
Spirogyra sp. is a green macroalgae that is found naturally in shallow freshwater. Spirogyra sp. is known to contain various chemical compositions that can be transformed to produce high-value bioproducts, one of which is the lipid fraction that contains omega-3 compound. Lipid levels in algae can be altered through the addition of heavy metal stress such as manganese. This study optimized the addition of Mn2+ (MnCl2.4H2O) to produce the highest lipid accumulation of Spirogyra sp. The study was designed using the Response Surface Methodology (RSM) approach to determine variations in Mn2+ concentration. Spirogyra sp. was cultivated for 14 days in BG-11 25% medium with final Mn2+ concentration of 2,3 (control); 2,5; 3,2; 4,8; 6,4; and 7,1 ?M. Cultivation conditions were at temperature of 25±3°C, light intensity of 2000-2500 lux, aeration of 0.2-0.4 L/minute, pH of 7,5±0.25, and light:dark photoperiodism of 16:8 hours. Destructive harvesting was carried out every two days to measure dry biomass and lipid levels by Bligh and Dyer extraction. Dry biomass and lipid content data were analysed using the kinetic model approach (logistic and Luedeking-Piret) and RSM. The results indicated that the addition of Mn2+ enhanced the growth and accumulation of lipid in Spirogyra sp. up to 1,2 and 2,3 times compared to control. Concentration testing of the RSM design resulted in the highest lipid content of 7,29 ± 0,20% and biomass of 0,79 ± 0,04 g in the addition of 5,1 ?M Mn2+. The highest productivity of biomass and lipid were also obtained from addition of 5,1 ?M Mn2+ with respective values of 117,88 ± 5,96 mg/L-day and 10,14 ± 0,61 mg/L-day. Lipid extract with the highest productivity was analysed by Gas Chromatography Mass Spectrometry (GC-MS) to identify its fatty acid profile. GC-MS analysis of lipid extract from the variation of 5,1 ?M Mn2+ detected the presence of ?-linolenic acid (omega-3) with a value of 20,5% fatty acids. The results of the growth model showed that the logistic equation can model the growth of Spirogyra sp. with a high correlation coefficient (R2>0,9) and the results of the Luedeking-Piret model suggested that lipid is a growth-associated product.